2020
DOI: 10.31557/apjcp.2020.21.11.3177
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of Toll-Like Receptors (TLR2 and TLR4) in Acute Myeloid Leukemia Patients

Abstract: About eleven human TLRs have been identified up till now and each of them participates in a specific intracellular signaling pathway. TLRs 1, 2, 4, 5 and 6 are typical for bacterial products, TLRs 3, 7 and 8 are characteristic for viral infection and TLR9 is associated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 21 publications
1
17
1
Order By: Relevance
“…Other studies have investigated the possible importance of TLR4 genetic polymorphisms and the clinical course for acute leukemia patients receiving intensive and potentially curative acute leukemia treatment: One study investigated eight single nucleotide polymorphisms (SNPs) in 194 children with acute lymphoblastic leukemia (ALL), and the four SNPs rs10759931, rs11536889, rs1927911 and rs6478317 were associated with increased risk of treatment-induced cytopenia [ 87 ]. The TLR4 Asp299Gly polymorphism seems to influence the risk of sepsis after AML therapy [ 88 ]. Another study also described an association between this SNP and the risk of both sepsis and pneumonia; the same associations were described for the Thr399Ile TLR4 polymorphism whereas the TLR2 polymorphism Arg753Gln was only associated with pneumonia [ 89 ].…”
Section: Tlr4 Mediated Immunoregulation In Aml; the Importance Of Gen...mentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have investigated the possible importance of TLR4 genetic polymorphisms and the clinical course for acute leukemia patients receiving intensive and potentially curative acute leukemia treatment: One study investigated eight single nucleotide polymorphisms (SNPs) in 194 children with acute lymphoblastic leukemia (ALL), and the four SNPs rs10759931, rs11536889, rs1927911 and rs6478317 were associated with increased risk of treatment-induced cytopenia [ 87 ]. The TLR4 Asp299Gly polymorphism seems to influence the risk of sepsis after AML therapy [ 88 ]. Another study also described an association between this SNP and the risk of both sepsis and pneumonia; the same associations were described for the Thr399Ile TLR4 polymorphism whereas the TLR2 polymorphism Arg753Gln was only associated with pneumonia [ 89 ].…”
Section: Tlr4 Mediated Immunoregulation In Aml; the Importance Of Gen...mentioning
confidence: 99%
“…On the other hand, another study described an association between invasive aspergillosis and the Asp299Gly/Thr399Ile variants in the donor or recipient after allogeneic stem cell transplantation [ 91 ]. The TLR4 Asp299Gly polymorphism was associated with relapse risk in one previous study [ 88 ], and a study of European children with ALL suggested an association between TLR6 SNPs and risk of leukemia [ 92 ]. …”
Section: Tlr4 Mediated Immunoregulation In Aml; the Importance Of Gen...mentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this evidence, it seems advantageous to continue research on TLR4 and its inhibitor, as it may be a good strategy for the treatment of TLR4-expressing AML in the future. Aref et al investigated the impact of TLR2 and TLR4 polymorphisms on the survival of patients with AML and their susceptibility to severe infections [ 293 ]. They demonstrated that, in AML patients with TLR2 Arg753Gln with an AG genotype and an A allele, TLR4 Asp299Gly with a CT genotype and a C allele, and TLR4 Thr399Ile with an AG genotype and an A allele, pneumonia and sepsis were more frequent than in patients with other genotypes and alleles.…”
Section: Future Perspectives In the Treatment Of All Or Amlmentioning
confidence: 99%
“…This study showed that, in these patients, TLR polymorphism translates into both their risk of infection and survival. However, more research is needed on this point [ 293 ].…”
Section: Future Perspectives In the Treatment Of All Or Amlmentioning
confidence: 99%